Baicalin-modified polyethylenimine for miR-34a efficient and safe delivery - Wang, Yingying; Wang, Baiyan; Xiao, Yangfan; Cai, Qingchun; Xing, Junyue; Tang, Hao; Li, Ruiqin; Zhang, Hongtao (Frontiers in Bioengineering and Biotechnology, 2023)
The success of gene therapy is inseparable from the development of safe and efficient gene carrier systems. The work provides a practical method to construct charge-regulated, hydrophobic modification, and functional polyethylenimine (PEI) with effective gene delivery and perfect transfection performance through condensation reaction, named BA-PEI. The carrier was shown to possess favorable compacted miRNA into positively charged nanoparticles with a hydrodynamic size around 100 nm. Additionally, BA-PEI possesses perfect degradability, which benefit the release of miR-34a from the complexes. Using the human lung cancer cell line A549 as a model, carrier/miR-34a transfection has been demonstrated to improve the expression level of the miR-34a gene by qPCR and western blotting. After the successful miR-34a gene delivery, the perfect antitumor ability of BA-PEI/miR-34a complex was systematic evaluation with suppressor tumor gene miR-34a systems in vitro and in vivo. In summary, the BA-PEI-mediated miR-34a gene transfection is advantageous over the commercial transfection reagent in safety and efficiency, therefore provides a new strategy to achieve miR-34a-based gene therapy.